The good Muslim: reflections on classical Islamic law and theology - Siddiqui, Mona (Cambridge Univ. Press, 2012)
"In this unusual, thought-provoking and beautifully written book, Mona Siddiqui reflects upon key themes in Islamic law or theology. She has selected these topics, which range through discussions about friendship, divorce, drunkenness, love, slavery, and ritual slaughter, in part because they are of particular interest to her, and in part because they reveal fascinating insights into Islamic ethics, and the way in which arguments developed in medieval juristic discourse. These pre-modern religious works contained a richness of thought, hesitation and speculation on a wide range of topics, which were socially relevant but also presented intellectual challenges to the scholars for whom God,♯s̥ revelation could be understood in diverse ways. These subjects of course remain very relevant today, both for practicing Muslims and for scholars of Islamic law and religious studies, and the book shows just how these debates resonate in contemporary Islamic thought. Mona Siddiqui is an astute and articulate interpreter who relays complex ideas about the Islamic tradition with great clarity. These are important attributes for a book which, as the author acknowledges, charts her own journey through the classical texts, and reflects upon how the principles expounded there have guided her own thinking and impacted on her teaching and research"--